2024
DOI: 10.1136/bmjgh-2023-014173
|View full text |Cite
|
Sign up to set email alerts
|

Colonisation and its aftermath: reimagining global surgery

Rennie Qin,
Barnabas Alayande,
Isioma Okolo
et al.

Abstract: Coloniality in global health manifests as systemic inequalities, not based on merit, that benefit one group at the expense of another. Global surgery seeks to advance equity by inserting surgery into the global health agenda; however, it inherits the biases in global health. As a diverse group of global surgery practitioners, we aimed to examine inequities in global surgery. Using a structured, iterative, group Delphi consensus-building process drawing on the literature and our lived experiences, we identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…Focus has now turned to locally championed interventions. 13 Inequities of global surgery were examined by Qin et al 14 They identified Western epistemology (established from colonialism), unequal participation, and geographic inequity as some of the barriers to inclusive global surgery. 14 The World Bank classifies South Africa as an upper-middleincome country.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Focus has now turned to locally championed interventions. 13 Inequities of global surgery were examined by Qin et al 14 They identified Western epistemology (established from colonialism), unequal participation, and geographic inequity as some of the barriers to inclusive global surgery. 14 The World Bank classifies South Africa as an upper-middleincome country.…”
Section: Introductionmentioning
confidence: 99%
“…13 Inequities of global surgery were examined by Qin et al 14 They identified Western epistemology (established from colonialism), unequal participation, and geographic inequity as some of the barriers to inclusive global surgery. 14 The World Bank classifies South Africa as an upper-middleincome country. 15 However, the country has one of the highest inequality rates described globally due to a large percentage of the population living below the upper-middle-income country poverty line.…”
Section: Introductionmentioning
confidence: 99%